AN ENDURING PLATFORM FOR PUBLIC AND COOPERATIVE ECONOMICS RESEARCH: A CENTENNIAL PERSPECTIVE. (10th February 2018) - MARINI, Marco; THIRY, Bernard
ABSTRACT: In this short introduction, after briefly remembering the exemplary role played by Edgard Milhaud for the birth and development of Annals, we describe the content of the current special issue devoted to the 110 years of the journal.